The Existence of Two Types of Colloidal Solutions of Molecules Fullerene C60 - Schur, D.V.; Yu. Zaginaichenko, S.; Veziroglu, T.N.; Veziroglu, A.; Gabdullin, M.T. (Journal of Applied Solution Chemistry and Modeling, 2015)
The last thirty years scientists carried out an active search of universal parameter of solvent C60 for predicting the solubility of fullerenes. However, this parameter was not found up to these days. In this paper it has been found an explanation of the impossibility of detection of such parameter. In present paper the features of the solubility of fullerene C60 molecules in nonpolar solvents have been studied. The molecule state diagram of the fullerene Ð¡60 molecules in solution at temperatures 265+308 K and pressure range 1+100 MPa indicating the existence field of β and γ-modifications, has been constructed. Moreover, it has been shown that in the solutions of fullerenes C60 in the γ-state the solubility decreases with a rise in temperature since the chemical activity of fullerene molecule increases. For this reason during extraction procedure the temperature rise causes the value of extraction rate to increase, but solubility â€“ to decrease, i.e. to diminish the concentration of fullerenes molecules in the solvent volume.